Titanium infiltration into ultrathin PMMA brushes - Mani Gonzalez, Pierre Giovanni (2021)
Vapor phase infiltration (VPI) is a bottom-up process that involves the infiltration of polymers, often using atomic layer deposition compatible precursors. By exposing a polymer to an organo-metallic precursor, area selective material formation is achieved where the precursor reacts with regions covered by an infiltration-receptive polymer brush. Combining receptive and rejecting polymers that have the capability of forming complex nanopatterns could potentially allow for the creation of nanofeatures, offering a route to area selective deposition. This work is concerned with the creation and characterization of titanium-infiltrated films with a VPI process. Thin films of poly(methyl methacrylate) (PMMA) were infused with titanium isopropoxide and subsequently analyzed with angular resolved x-ray photoelectron spectroscopy. All XPS analysis and VPI treatments were completed without breaking vacuum in an integrated …